Evaluation of the Effectiveness of AI-Assisted Project-Based Learning on Research Proposal Writing Skills - Yunita Wardianti; Dian Samitra; Deo Alfa Riski (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Improving the quality of research proposals is a challenge in Biology education at the tertiary level. Integrating project-based learning with artificial intelligence (AI) support offers an innovative approach to strengthening students’ proposal writing skills. This study aimed to determine the effect of AI-assisted project-based learning on the ability to write research proposals of Biology Education students. Methodology: This study used a pretest-posttest quasi-experiment design with a control group. Two classes of Biology Education students were purposively selected. The experimental class applied AI-assisted project learning, while the control class used conventional methods. Data were collected through the assessment of the research proposal rubric and analyzed by t-test to assess the difference between the scores of the control class and experimental classes’ scores. The data obtained in this study were analyzed using SPSS. Main Findings: The research finding show that the average score of the experimental class proposal writing ability of 86.2 is greater than that of the control class proposal writing ability of 78.7. The results also show that the Sig. 0.0001 is smaller than 0.05, meaning that AI-assisted project-based learning affects the ability to write research proposals. This finding indicates that AI effectively supports students in designing and writing better research proposals. Novelty/Originality of this study: Research on the use of AI in project learning to improve research proposal writing skills is still limited. This study contribute that AI effectively supports students in designing and writing better research proposals.